DURATION LIMIT OF LASER PULSES EMITTED FROM A Ce-DOPED CRYSTAL SHORT CAVITY - Le Hoang Hai; Nguyen Dai Hung; Hoang Huu Hoa; Alex V. V. Quema; Nobuhiko Sarukura (Universitas Gadjah Mada, 2007)
Based on the rate equation set for broadband cavities, the dependence of pulse duration on cavity and pumping parameters is analyzed. The cavity uses a Ce-doped crystal as a gain medium. Computation results show the variation of the pulse width with the change of cavity length, mirror reflectivity, pumping energy and pumping pulse duration. A significant influence of multiple-pulse operation in limiting pulse duration is realized and a pulse-width of the order 200 ps is found to be the limit for the direct generation of ultraviolet single picosecond pulses from a Ce:LLF short cavity.